PENGARUH PEMBERIAN EKSTRAK ETANOL DAGING BUAH KECAPI (Sandoricum koetjape) TERHADAP KADAR KOLESTEROL TOTAL MENCIT (Mus muscullus) - Djajanti, Agust Dwi Djajanti; Ranteallo, Novita; Prayitno, Suprapto (Jurnal Kesehatan Yamasi Makassar, 2023)
This study aims to determine the effectiveness of the fruit flesh extract of Kecapi (Sandoricum koetjape) on reducing total cholesterol levels in mice (Mus muscullus). The research design used was an experimental laboratory which was carried out at the Pharmacology Laboratory of the Pancasakti University Makassar. This study used 15 male mice which were divided into 5 treatment groups, each group consisted of 3 mice. Test animals were fasted for 3-4 hours before treatment, all groups were given Propylthiouracil 0.4761% for 10 days. Then on the 10th day, cholesterol levels were checked after being induced. After that, treatment was given, namely, group I was given Na CMC as a negative control, group II was given simvastatin suspension as a comparison, group III was given harp fruit pulp extract with a concentration of 0.014% w/v, group IV was given harp fruit pulp extract with a concentration of 0.0285 %,, group V was given harp fruit pulp extract with a concentration of 0.057%. The process of reducing total cholesterol was observed on the 9th day. The results showed that the statistical test showed a significantly different effect (P<0.05) where the harp fruit pulp extract had a significant effect, which means that there was a cholesterol-lowering effect in mice. The highest concentration of harp fruit pulp extract in reducing total cholesterol levels in mice was at a concentration of 0.057% w/v compared to concentrations of 0.028% w/v and 0.014% w/v, because it provided the largest reduction in cholesterol levels, namely 53.74%.